JURIDICAL REGIME OF THE ORDINANCES IN THE ROMANIAN CONSTITUTIONAL REGIME - Oana ŞARAMET; S. G. BARBU (Bulletin of the Transilvania University of Braşov • Vol. 3 (52) - 2010, Series VII: Social Sciences • Law, 2010)
Legislative delegation is known in all constitutional systems of the democratic States as a means of co-operation between the legislative power and the executive power, to the purpose of achieving the interest of society. This institution represents the mandate for a certain well-delimited period of time and under conditions rigorously stipulated by the law, of another authority than the legislative one, to execute legislative prerogatives.
Keywords: legislative delegation; constitutional; legislative prerogatives.